From Death to Life – The Hydrological Circle of Cosmos and Copulation - Oestigaard, Terje (Dhaulagiri Journal of Sociology and Anthropology, 2008)
When a person dies, how is the soul transferred from the dead body to an infant in a mother's womb? In Hinduism this process in understood and explained metaphorically by the hydrological circle and the interrelatedness of fire and water. The cosmological circle of reincarnation is a life-giving process which includes the life-giving waters; the essence of life. Based on mythology and the sacred scriptures, this process is investigated. Key Words: Hindu Mythology, eroticism, funeral practice, sexuality DOI = 10.3126/dsaj.v2i0.1360 Dhaulagiri Journal of Sociology and Anthropology Vol.2 pp.121-144